Incidence of H1N1 2009 Virus Infection through the Analysis of Paired Plasma Specimens among Blood Donors, France - Bone, Angie; Guthmann, Jean-Paul; Assal, Azzedine; Rousset, Dominique; Degeorges, Armelle; Morel, Pascal; Valette, Martine; Enouf, Vincent; Jacquot, Eric; Pelletier, Bertrand; Le Strat, Yann; Pillonel, Josiane; et al. (PloS one, 2012)
Knowledge of the age-specific prevalence of seroprotection and incidence of seroconversion infection is necessary to complement clinical surveillance data and statistical models. It provides the basis for estimating the future impact of influenza A (H1N1pdm09) and implementing appropriate prevention and response strategies. Using a cross-sectional design, two-stage stratified sampling and paired plasma samples, we estimated the age-specific prevalence of a protective level of H1N1pdm09 antibodies in the French adult population before and after the 2009/10 pandemic, and the proportion of those susceptible that seroconverted due to infection, from a single sample of 1,936 blood donors aged 20-70 years in mainland France in June 2010. Samples with a haemagglutination inhibition (HI) titre ≥1∶40 were considered seropositive, and seroconversion due to infection was defined as a 4-fold increase in titre in the absence of H1N1pdm09 vaccination or pre-pandemic seropositivity. Out of the 1,936 donors, 1,708 were included in the analysis. Seroprevalence before the pandemic was 6.7% (95% CI 5.0, 8.9) with no significant differences by age-group (p = 0.3). Seroprevalence afterwards was 23.0% (95% CI 17.7, 29.3) with 20-29 year olds having a higher level than older groups (p<0.001). Seroconversion due to infection was 12.2% (95% CI 6.9, 20.5). Younger age-group, vaccination against H1N1 and being seropositive before the pandemic were strongly associated with post-pandemic seropositivity. Before the 2009/2010 winter influenza season, only 6.7% of the French mainland population aged 20-70 had a level of antibodies usually considered protective. During the first pandemic wave, 12.2% of the population seroconverted due to infection and the seroprevalence after the wave rose to 23%, either due to prepandemic seropositivity, infection or vaccination. This relatively low latter figure contributed to an extension of target groups for influenza vaccination for the 2010/2011 season.